The Chosen City Conquest and Sanctification Traditions of Jerusalem - Ṿazanah, Nili (2017)
The account of the conquest of Jerusalem from 'the Jebusites who inhabited the region' (2Sam 5,6) should be understood historically in the context of the reconstruction of the beginnings of Israel in the land, like other biblical conquest traditions. At the same time, the literary uniqueness of this account reflects the ideological role of Jerusalem within the Deuteronomistic cycles — Jerusalem is like no other. The story of its conquest and establishment as the Israelite capital will be reconsidered here in light of the role played by the city in other conquest narratives, and in narratives of the foundation of holy sites.